THE ROLE OF ARTIFICIAL INTELLIGENCE AND MODERN INFORMATION TECHNOLOGIES IN THE LIFE OF SOCIETY AND PROSPECTS FOR THEIR DEVELOPMENT (Web of Teachers: Inderscience Research, 2025)
This article analyzes the transformations that have occurred over the past decades in the field of artificial intelligence and modern information technologies, as well as their impact on education, healthcare, the economy and the social sphere. radicalization processes. The results of the study help to determine the importance of artificial intelligence in the development of society and ways to use it safely and effectively.